Revisiting the Dimensions of Knowledge Management Orientation Behavior in Indonesia Creative Industry - Sabil Hussein, Ananda; Rahayu, Mintarti; Prabandari, Sri Palupi; Rosita, Nadiyah Hirfiyana (International Research Journal of Business Studies, 2016)
This study aims to explore the formation of knowledge management orientation behaviour (KMO) in Indonesian creative industry. To answer the research objective, two consequtive studies were conducted. The first study intends to generate the measurement items. Two registered Focus Group Discussions (FGDs) with eight participants for each session were held. Upon the completion of FGDs, a survey into 171 respondents was done , and the Exploratory Factor Analysis (EFA) was employed to analyse the data. The second study objective is to confirm the measurement items that have been generated from the FGDs . A survey into 174 respondents was conducted, and confirmatory Factor Analysis was employed to analyse the data. The finding confirms that organizing memory development, organizing memory support system, knowledge sharing, knowledge absorption and knowledge receptivity are the dimensions of KMO in Indonesian creative industry. Upon the completion of this study, both theoretical and practical contributons are provided to bring an insight for creative industry practitioners to apply KMO in their business.